2013
DOI: 10.3357/asem.3405.2013
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging Anomalies in U-2 Pilots with Neurological Decompression Sickness

Abstract: P. Brain magnetic resonance imaging anomalies in U-2 pilots with neurological decompression sickness.Aviat Space Environ Med 2013; 84:3-11.Introduction: This was a retrospective observational study of imaging used to evaluate and treat 13 U-2 pilots with neurological decompression sickness (DCS). Magnetic resonance imaging (MRI) and computed tomography (CT) provided data for screening, diagnosis, and determinations of fi tness to fl y after recovery. While small series and case reports described the role of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In patients with AGE, air gas occludes large arteries and causes territorial infarction. In contrast, MRI has a low sensitivity for the diagnosis of cerebral DCS not only in divers but also in aviators [ 9 ]. A neuropathological examination showed that DCS caused subtle and diffuse changes in the brain with no large areas of necrosis, including grossly dilated empty vessels in the white matter, small areas of focal necrosis in the gray matter, and diffusely distributed areas of vacuolation of the myelin around small blood vessels [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with AGE, air gas occludes large arteries and causes territorial infarction. In contrast, MRI has a low sensitivity for the diagnosis of cerebral DCS not only in divers but also in aviators [ 9 ]. A neuropathological examination showed that DCS caused subtle and diffuse changes in the brain with no large areas of necrosis, including grossly dilated empty vessels in the white matter, small areas of focal necrosis in the gray matter, and diffusely distributed areas of vacuolation of the myelin around small blood vessels [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The report carries an impressive bibliography, with more than 230 sources cited. However, the committee concurs with the 2014 DCS Risk Standing Review Panel (Steinberg et al, 2014) that additional literature review areas could strengthen the report: Jersey et al, 2013;McGuire et al, 2013;Pilmanis et al, 2010) • A review of research focusing on human adaptation to hypoxic and high-altitude environments • Work on pre-breathe interruption (Conkin, 2011;Pilmanis et al, 2010) • Work by Buckey and colleagues on DCS instrumentation (Buckey et al, 2005) Please refer to the 2014 DCS Standing Review Panel for detailed citation suggestions (Mahon et al, 2014).…”
Section: Is the Breadth Of The Cited Literature Sufficient?mentioning
confidence: 98%
“…• Work by Thom and colleagues at University of Maryland on micronuclei particles • Work by Flagg and colleagues on pre-breathe interruption • Work by the U.S. Navy at the Navy Experimental Diving Unit and Naval Submarine Research Lab relating to EVA operations and limited resource allocation • Reports on the U.S. Air Force Manned Orbital Laboratory Program focusing on manned long-term low-pressure exposures • Specific research related to U2-pilot DCS (e.g., Jersey et al, 2013;McGuire et al, 2013;Pilmanis et al, 2010) • A review of research focusing on human adaptation to hypoxic and high-altitude environments • Work on pre-breathe interruption (Conkin, 2011;Pilmanis et al, 2010) • Work by Buckey and colleagues on DCS instrumentation (Buckey et al, 2005) Please refer to the 2014 DCS Standing Review Panel for detailed citation suggestions .…”
Section: Is the Breadth Of The Cited Literature Sufficient?mentioning
confidence: 99%